2013
DOI: 10.1103/physrevc.88.014906
|View full text |Cite
|
Sign up to set email alerts
|

Noncongruence of the nuclear liquid-gas and deconfinement phase transitions

Abstract: First order phase transitions (PTs) with more than one globally conserved charge, so-called noncongruent PTs, have characteristic differences compared to congruent PTs (e.g., dimensionality of phase diagrams, location and properties of critical points and endpoints). In the present article we investigate the non-congruence of the nuclear liquid-gas PT at sub-saturation densities and the deconfinement PT at high densities and/or temperatures in Coulomb-less models, relevant for heavyion collisions and neutron s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 122 publications
(263 reference statements)
4
102
0
Order By: Relevance
“…[32,33,40,42], it was shown that the slope dP=dTj PT is negative for the QCD phase transition and positive for the liquid-gas phase transition of nuclear matter (see also Refs. [35,36,43]).…”
Section: Relation To the Qcd Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…[32,33,40,42], it was shown that the slope dP=dTj PT is negative for the QCD phase transition and positive for the liquid-gas phase transition of nuclear matter (see also Refs. [35,36,43]).…”
Section: Relation To the Qcd Phase Diagrammentioning
confidence: 99%
“…The reason for this special property of the QCD phase transition can be identified by using the ClausiusClapeyron equation [27,32,33,40,43],…”
Section: Relation To the Qcd Phase Diagrammentioning
confidence: 99%
“…Therefore, , which is the opposite of its behavior in the nuclear liquid-gas phase transition, sometimes called an "entropic" phase transition (cf. Hempel et al 2013;Iosilevskiy 2013, Iosilevskiy 2015 andreferences therein). This property could lead to interesting consequences for neutron stars and core-collapse supernovae Yudin et al 2016).…”
Section: Bdcmentioning
confidence: 99%
“…For this purpose, we extended the hadronic SU(3) non-linear realization of the sigma model, see e.g. [20,21,22,23], to include quark degrees of freedom in a spirit similar to the PNJL model ( [24]), in the sense that it uses the Polyakov loop Φ as the order parameter for deconfinement. The Lagrangian density of the model in mean field approximation reads:…”
Section: Magnetized Equation Of Statementioning
confidence: 99%